Cardiac magnetic resonance in systemic sclerosis: imaging features and potential prognostic implications. A literature review - Vitale, Giovanni; Colina, Matteo; Attinà, Domenico; Niro, Fabio; Ortolani, Paolo (Frontiers in Medicine, 2025)
Systemic sclerosis (SSc) is a chronic, multisystem disorder characterized by vascular dysfunction, immune dysregulation with production of autoantibodies, fibroblasts dysfunction and consequent abnormal collagen production, leading to progressive fibrosis of the skin and various organs. Cardiac involvement is common, affecting the myocardium, pericardium, valvular structures and conduction tissue, even though it is often unrecognized. Despite this, it is a major determinant of morbidity and mortality in SSc, being responsible for about 15% of all deaths. Due to the relevant prognostic implications of cardiac involvement its early detection is mandatory. A comprehensive screening through a multimodality approach is required in all patients with SSc, even in those without overt cardiac symptoms. Cardiac magnetic resonance (CMR) is now considered the gold standard for non-invasive detection of the myocardial disease SSc related. It provides not only a morphological and functional assessment, but also offers an ultrastructural definition of the myocardium, particularly by the detection of fibrosis and myocardial inflammation (MI), unmasking an initial myocardial involvement since the early stage of disease. The aim of this review is to describe the potential spectrum of cardiac involvement in SSc, and to highlight central role of CMR in its detection, offering a comprehensive description of the imaging features and their prognostic implication.